Educating T-shaped Design, Business and Engineering Professionals - Karjalainen, T-M.; Koria, M.; Salimäki, M. (Cranfield University Press, 2009)
The paper provides an insight into the International Design Business Management Program (IDBM), an attempt to educate T-shaped professionals who can combine design, business and technology knowledge. IDBM is creating a new master program, in which solid theoretical basis, delivery methods, and structure are being developed to improve both coherence and relevance within the curriculum. To contribute to the coherence of systemic competence development, a model of five major dimensions – tools, environment, management, process, organisation (TEMPO) – is proposed. To ensure the relevance of the program, four professional orientation tracks are built into the curriculum; research, management, consulting and entrepreneurship.
Organised by: Cranfield University
Keywords: Multidisciplinary Education; Systemic Competence; Curriculum Development; Design Strategy